Foreign policy in times of progressivism - Diamint, Rut (2018)
Twelve years after the resurgence of the left in Latin America, we are now witnessing its dawn and the emergence of the right. In the present article, the author asks if this situation responds to a situational crisis of the progressive governments of Latin America or, if in reality, we are witnessing the failure of these alternative projects that only produced cosmetic changes. The author analyzes the failed attempt to create new rules in the international system, national politics and the regional construction by the progressive governments, because of the use of outdated means —based on schemes and concepts of the Cold War— in a different global context. The article begins with a general exposition of the progressive proposals to later analyze the cases of Brazil and Venezuela, ending with conclusions of the main hypothesis.